Desarrollo de una nano-plataforma basada en puntos de carbono co-dopados con N y Gd3+ como potencial agente radio-sensibilizante (2021)
(ing) Cancer is one of the main causes of death in the world, and it is treated from different approaches or clinical treatments, seeking to eliminate or reduce the size of the tumor. Radiotherapy is one of the most used treatments, and its objective is to induce cell death as a consequence of DNA chain breaks produced by ionizing radiation. However, radiation affects both tumor cells and healthy cells, producing harmful side effects for the patient. Despite the great advances in the generation of radiotherapy technologies, it is necessary to develop new strategies that allow radiation to be concentrated in tumor tissues and reduce interaction with healthy tissues. These effects can be achieved through the development of radiosensitizing or radioprotective agents, respectively. Carbon points (CPs) are an option for the development of new strategies. These nanoparticles based mostly on sp2/sp3 carbons reported as biocompatible, present colloidal impermeable stability, exhibit fluorescence, and can be used as a basis for the design of radiosensitizing agents. In order to increase the efficiency of radiotherapy, this paper presents the synthesis, characterization and preliminary cytotoxicity studies of a nano-platform based on carbon dots co-doped with N and Gd3+ (PC:N/Gd3+), as the initial phase of the development of a potential radiosensitizing agent. The incorporation of the Gd3+ ion increases the electronic density due to the high atomic number of this ion and consequently the probability of interaction with the radiotherapy photons. In addition, most PCs exhibit intrinsic fluorescence in the UV-blue range of the electromagnetic spectrum, a region where several endogenous fluorophores in human tissues have high absorption coefficients. For this reason, it is proposed to include organic nitrogen sources in the synthesis process, favoring the generation of PCs capable of emitting fluorescence at longer wavelengths where tissue autoflorescence is lower.